The Omc in the European Employment Policy: Bringing Socialisation In - Matia Vannoni (CES Working Papers, 2011)
This paper argues in favour of a more thorough analysis of a specific set of dynamics taking place in the Open Method of Coordination (OMC), the latter being conceived as an informal organizational framework aimed at mutual learning (de Burca and Zeitlin, 2003) and policy change (Dolowitz and Marsh, 2000; Radaelli, 2000). The aim of this paper is to uncover the missing link between these two elements, which has hitherto been black-boxed by the literature. Theoretical tools from International Relations (IR) theories (i.e. constructivist institutionalism) are borrowed in order to circumvent such a fallacy. The premises are the same as the ones hitherto employed by scholars studying the OMC (e.g. Jacobsson, 2004): can norms and values assume a binding character even outside the `territorially bounded democratic government' (Héritier and Lehmkuhl, 2008) and thus leading to policy change? If so, how does this phenomenon take place? Nevertheless, the approach is different, in that it builds on two closely interrelated factors: the concept of socialisation with its micro-processes (Johnston, 2001; Johnston, 2008) and the institutional characteristics of social environments (Rogowski, 1999). Accordingly, this paper will address the question: is the OMC in European employment policy a social environment conducive of socialisation?
Keywords: 330; Open Method of Coordination; mode of governance; policy learning; socialisation Romania